Overreaction Anomaly on Indonesia Stock Exchange in The JII70 Index for 2020-2022 - Thomas, Jericho; Akbar, Masithah; Bachtiar, Yanuar; Nastiti, Rizky; Anuar Syahdan, Saifhul (Asosiasi Dosen Akuntansi Indonesia, 2024)
This research aims to analyse the phenomenon of overreaction anomaly, characterised by differences in cumulative average abnormal returns between winner stock portfolios and loser stock portfolios on the Indonesia Stock Exchange (BEI). The sample used in the research included shares of companies in JII70 and was selected using purposive sampling techniques to obtain 12 company shares. The method for calculating abnormal returns in this research uses the market-adjusted model. In addition, an independent sample t-test was chosen as a statistical test to test the difference between cumulative average abnormal return winners and cumulative average abnormal return losers. The results of this study show that the overreaction anomaly phenomenon of the three formations (monthly, quarterly, and semester) only occurs in the monthly formation.